Unintended Consequences in Transformative Service Research: Helping Without Harming. (February 2022) - Blocker, Christopher P.; Davis, Brennan; Anderson, Laurel
Even as transformative service initiatives promote greater well-being, they may also create unintentionally negative consequences. Research investigates boundary conditions and boomerang effects that wash out or reverse the intended effects of service initiatives. However, such research generally advances greater depth of insight about unintended consequences in a particular stream rather than bridging this knowledge across service domains. Thus, service research lacks integrative frameworks, theory, and empirical insight to advance more generalizable knowledge about unintended consequences. The purpose of this editorial is to clarify the importance of investigating unintended consequences across service contexts and propose pathways as a catalyst for research. Using theory on unintended consequences, we delineate the types of unintended consequences and discuss the underlying mechanisms. We identify themes that span papers in the special issue and illuminate negative spillover consequences. The editorial concludes with an overview of future research avenues with potential to accelerate important transformative service research.